Improvement of hepatic microhemodynamics by n-acetylcysteine after warm ischemia - Koeppel, Thomas; Thies, Jochen; Lehmann, Thorsten G.; Gebhard, Martha-Maria; Herfarth, Christian; Otto, Gerd; Post, Stefan (European surgical research, 1996)
In this study we investigated the influence of N-acetylcysteine (NAC) on the hepatic microcirculation after warm ischemia by intravital fluorescence microscopy. Clamping of the left liver lobe was performed in 20 male Wistar rats for 70 min. The treatment group (n = 10) received 400 mg NAC/kg body weight 20 min prior to clamping. After reperfusion, acinar and sinusoidal perfusions were observed as well as the leukocyte-endothelium interaction. Phagocytic activity was assessed after application of latex beads. NAC reduced the number of nonperfused sinusoids in all acinar zones. A reduction in zone (portal) was achieved from 15.5 to 7. l%(p < 0.0001), in zone (midzonal) from 14.6 to 6.1% (p < 0.0001) and in zone 3 (central) from 11.9 to 2.9% (p < 0.0001). There were no significant differences in leukocyte adherence as well as in phagocytic activity detectable. We conclude that NAC improves hepatic microcirculation after warm ischemia by increasing sinusoidal blood flow.
Elektronische Reproduktion der Druck-Ausgabe 24. April 2008
Gesehen am 03.09.2025